Physiotherapy in mental health and psychiatry a scientific and clinical based approach - Probst, Michel; Skjaerven, Liv Helvik (Physiotherapy essentials., 2018)
A brand new and must have textbook for the students and practising physiotherapists which acts as a trusted guide on the different perspectives, contexts and approaches across the spectrum of mental health and psychiatry settings. Grounded in theory and clinical practice, it covers a range of widely-used evaluation tools and treatment methods for specific syndromes and pathologies which will help physiotherapists to signpost and identify the care needs of their patients within both individual and group therapeutic settings. Case studies ensure that the theory discussed is applied to various practical scenarios after which reflective exercises are used to reinforce learning and understanding."--.